Effect of alkaline treatment on mechanical and thermal properties of miswak (Salvadora persica) fiber reinforced polylactic acid - Ayu Rafiqah, S.; Nur Diyana, A. F.; Abdan, Khalina; Sapuan, S. M. (Multidisciplinary Digital Publishing Institute, 2023)
This study examines the effects of alkaline treatment on the mechanical and thermal properties of miswak fiber-reinforced polylactic acid. The treatment was performed with three distinct concentrations of sodium hydroxide (NaOH): 1 wt %, 2 wt %, and 3 wt %. The difficulties of interaction between the surface of the fiber and the matrix, which led to this treatment, is caused by miswak fiber’s hydrophilic character, which impedes its ability to bind with hydrophobic polylactic acid. FTIR, tensile, TGA, and DMA measurements were used to characterize the composite samples. A scanning electron microscope (SEM) was used to examine the microstructures of many broken samples. The treatment is not yet especially effective in enhancing interfacial bonding, as seen by the uneven tensile strength data. The effect of the treated fiber surface significantly improves the tensile strength of miswak fiber-reinforced PLA composites. Tensile strength improves by 18.01%, 6.48%, and 14.50%, respectively, for 1 wt %, 2 wt %, and 3 wt %. Only 2 wt %-treated fiber exhibits an increase of 0.7% in tensile modulus. The modulus decreases by 4.15 % at 1 wt % and by 19.7% at 3 wt %, respectively. The TGA curve for alkali-treated fiber composites demonstrates a slight increase in thermal stability when compared to untreated fiber composites at high temperatures. For DMA, the composites with surface treatment have higher storage moduli than the composite with untreated miswak fiber, especially for the PLA reinforced with 2 wt % alkali miswak fiber, proving the effectiveness of the treatment.